2021
DOI: 10.1186/s13031-021-00377-2
|View full text |Cite
|
Sign up to set email alerts
|

Conflict-related violence and mental health among self-settled Democratic Republic of Congo female refugees in Kampala, Uganda – a respondent driven sampling survey

Abstract: Background Violence and traumatic events are highly prevalent among refugees, but less is known about the impact of these experiences among self-settled refugees in the country of asylum. We evaluated the association between traumatic experiences and PTSD and depression symptoms among female Democratic Republic of Congo (DRC) refugees living in Kampala, Uganda. Methods Participants were recruited using respondent driven sampling in one refugee serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Both diagnostic and screening tools were used to assess depression among different populations in Uganda ( Table 1 ). The tools used included: (i) Depression sub-section of the Hopkins Symptom Checklist (DHSCL) ( n = 34, 26.8%) [ 35 , 55 , 61 , 63 , 65 68 , 71 , 73 , 74 , 79 82 , 84 , 92 , 100 , 108 , 110 , 111 , 113 , 125 , 135 , 136 , 138 , 140 , 141 , 144 , 147 , 151 , 155 , 166 ], (ii) Patient Health Questionnaire (PHQ) ( n = 33, 26.0%) [ 16 , 21 , 32 , 34 , 36 , 37 , 52 , 86 , 88 90 , 93 , 98 , 99 , 101 , 102 , 112 , 116 118 , 120 123 , 126 128 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both diagnostic and screening tools were used to assess depression among different populations in Uganda ( Table 1 ). The tools used included: (i) Depression sub-section of the Hopkins Symptom Checklist (DHSCL) ( n = 34, 26.8%) [ 35 , 55 , 61 , 63 , 65 68 , 71 , 73 , 74 , 79 82 , 84 , 92 , 100 , 108 , 110 , 111 , 113 , 125 , 135 , 136 , 138 , 140 , 141 , 144 , 147 , 151 , 155 , 166 ], (ii) Patient Health Questionnaire (PHQ) ( n = 33, 26.0%) [ 16 , 21 , 32 , 34 , 36 , 37 , 52 , 86 , 88 90 , 93 , 98 , 99 , 101 , 102 , 112 , 116 118 , 120 123 , 126 128 , …”
Section: Resultsmentioning
confidence: 99%
“…Depression was screened or diagnosed in the following study groups in Uganda: (i) individuals living with HIV ( n = 43) [ 15 , 34 , 60 , 64 , 68 , 70 73 , 79 , 81 , 82 , 85 91 , 93 96 , 98 105 , 112 114 , 117 , 119 , 123 , 127 , 128 , 130 , 132 , 133 , 136 , 141 143 , 145 , 148 150 , 160 ], (ii) females only ( n = 25) [ 16 , 31 , 35 , 52 , 59 , 73 , 79 , 97 , 113 , 116 , 134 , 139 , 144 , 158 , 166 , 170 ], including seven studies among pregnant or postpartum women [ 53 , 59 , 73 , 97 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Available data show a high burden of IPV and mental health problems in humanitarian settings. In line with these global findings, a strong correlation between experiences of IPV and worse mental health outcomes has also been found among Congolese refugee women (Familiar et al, 2021;Morof et al, 2014;Sipsma et al, 2015). This study uses data collected from Congolese survivors of IPV living in Nyarugusu Refugee Camp, Tanzania-a population and humanitarian context with high documented burden of IPV and associated mental health problems (Greene et al, 2016;Johnson et al, 2010;Lugova et al, 2020;Norman & Niehuus, 2015;Schmitt et al, 2021;Tankink et al, 2010).…”
Section: Introductionmentioning
confidence: 78%
“…Sexual violence is particularly likely to lead to poor mental health (Cortina & Kubiak, 2006 ; Kessler et al, 2017 ). Although much of the literature on Congolese refugees has focused on the impacts of rape on women (Ainamani et al, 2020 ; Familiar et al, 2021 ), population-based research with conflict-affected people in DRC (Johnson et al, 2010 ) indicated that 23.6% of males had also experienced sexual violence. For this reason, in addition to the number of conflict-related PTEs, we looked specifically at the association between sexual violence and distress for both males and females.…”
Section: Introductionmentioning
confidence: 99%